Use of the Diabetes Medication Choice Decision Aid in patients with type 2 diabetes in Greece: a cluster randomised trial. Issue 11 (14th November 2016) - Karagiannis, Thomas; Liakos, Aris; Branda, Megan E; Athanasiadou, Eleni; Mainou, Maria; Boura, Panagiota; Goulis, Dimitrios G; LeBlanc, Annie; Montori, Victor M; Tsapas, Apostolos
Abstract : Objective: To assess the efficacy of the Diabetes Medication Choice Decision Aid among patients with type 2 diabetes in Greece. Design: Open-label cluster randomised controlled trial. Setting: Primary and secondary care practices across Greece. Participants: 5 sites allocated to the decision aid (n=101 patients) and 4 sites to control (n=103 patients). Intervention: Clinicians and patients in the intervention arm used a decision aid, based on outcomes that both consider important when choosing among antihyperglycaemic medications. Patients in the control arm received usual care. Outcome measures: The primary outcome was patient's level of decisional comfort after the initial clinical encounter. Secondary outcomes included patient's knowledge about type 2 diabetes and medications, and patient's and clinician's satisfaction. Adherence to prescribed antihyperglycaemic medication and change in glycated haemoglobin were assessed at 24 weeks. Results: Patients in both arms had similar scores in overall decisional comfort (mean difference between the usual care and decision aid arms −6.9, 95% CI −21.5 to 7.7) and its subscales. Patients' knowledge was high in both arms (mean difference 2.3%, 95% CI −15.7% to 20.4%). Patients and clinicians in both groups were equally satisfied with the decision-making. No significant difference in medication adherence and glycaemic control was found across arms. Clinicians found the decision aid useful and reported that its integration in their daily routine was easy. Conclusions: The decision aid was implemented and positively received in the clinical setting in Greece, in line with the patient-centred approach endorsed by current guidelines. However, this trial yielded imprecise results in terms of patient outcomes. Further research is needed to investigate the interaction between the patient and the clinician in order to clarify the association between the use of decision aids and implementation of shared decision-making. Trial registration number: NCT01861756 . Pre-results.